Principles of protein structure: an established Internet-based course in structural biology - Clare Sansom; David Moss (Association for Learning Technology, 2000)
The Internet is becoming an important medium for the delivery of educational materials. However, relatively few institutions are delivering whole courses using this medium. More often, the technologies are used to complement traditional courses, which may be given face-to-face or at a distance (Farrell, 1999). The Department of Crystallography at Birkbeck College, London, has been in the vanguard of the development of 'virtual education', providing some of the first accredited postgraduate courses in the UK to be offered entirely using the new technologies. For the past four years, we have been running an Advanced Certificate course entitled 'Principles of Protein Structure using the Internet'1 (Sansom, Walshaw and Moss, 1997) (PPS). See http://www.cryst.bbk.aauk/pps for more details. This was one of the first tutor-assisted, accredited, university-level courses to be taught entirely over the Internet, and is certainly the first in biochemistry in the UK.